A review of current strategies to improve HIV prevention and treatment in sexual and gender minority Latinx (SGML) communities. Issue 3 (4th March 2021) - Martinez, Omar
ABSTRACT: Introduction: The HIV epidemic continues to disproportionately impact sexual and gender minority Latinxs (SGML). Several syndemic conditions have been linked with HIV acquisition and transmission among SGML including immigration, discrimination, environmental racism, substance use, and mental health. Areas covered: We provide a summary of biomedical, behavioral, and social/structural interventions to reduce risks for acquiring HIV and improve outcomes along the HIV care continuum among SGML. We also discuss intervention approaches and opportunities that respond at the intersection of HIV and COVID-19 prevention and treatment. Expert opinion: There is a dire need for the combination of biomedical, behavioral, and social/structural interventions to reduce risks for acquiring HIV and improve outcomes along the HIV care continuum. Interventions and combination approaches should be driven by community-based participatory action research. The inclusion of community members in all stages of the research process can assure successful implementation of program activities and deliverables, including the provision of culturally and linguistically appropriate services. Given the current COVID-19 pandemic, which is disproportionately impacting individuals living with HIV and other comorbidities, the elderly, and under-resourced communities with a ferocity not seen in other communities, intervention approaches that respond at the intersection of HIV and COVID-19 prevention and treatment are also urgently needed.